Physical activity and cognitive function in middle-aged adults: a cross-sectional analysis of the PATH through life study - Quinlan, Clare; Rattray, Ben; Pryor, Disa; Northey, Joseph M.; Cherbuin, Nicolas (Frontiers in Psychology, 2023)
Objectives: Investigate the independent associations of objectively measured or self-reported physical activity at different intensities, with cognitive performance in middle-aged adults. Design: cross-sectional. Methods: 156 middle-aged adults (age: 40.6 ± 1.5, 58.3% female) participated in the physical activity sub-study of the Personality and Total Health through life (PATH) project. Physical activity was measured objectively with the SenseWear™ armband (SWA), worn for seven consecutive days, and measured via self-report with a Physical Activity Recall survey (PAR). Cognitive performance was assessed with the Symbol Digit Modalities Test, the Digit Span Backwards, and an Immediate and Delayed Recall task. Associations between physical activity intensity and cognitive function were investigated in general linear models, controlling for age, sex, and education. Results: Neither objectively measured nor self-reported physical activity were associated with cognitive function at light-, moderate-, vigorous-, or combined moderate-to-vigorous intensity in this cohort of well educated, healthy middle-aged adults. Sensitivity analyses with additional moderators (e.g., body mass index, hypertension, alcohol intake) and the use of composite cognitive measures did not alter the results. Conclusions: In this cohort of middle-aged adults, objectively measured and self-reported physical activity do not appear to be associated with cognitive function . Longitudinal follow-ups utilising objective physical activity measures may be important in determining the impact of mid-life behaviours on the trajectory of cognitive changes into older age.